Looking Precisely at Your Fingertip Requires Visual Guidance of Gaze. (November 2020) - Kuling, Irene A.; Laan, Lotte; Lopik, Erik van; Smeets, Jeroen B. J.; Brenner, Eli
People often look at objects that they are holding in their hands. It is therefore reasonable to expect them to be able to direct their gaze precisely with respect to their fingers. However, we know that people make reproducible idiosyncratic errors of up to a few centimetres when they try to align a visible cursor to their own finger hidden below a surface. To find out whether they also make idiosyncratic errors when they try to look at their finger, we asked participants to hold their finger in front of their head in the dark, and look at it. Participants made idiosyncratic errors of a similar magnitude to those previously found when matching a visual cursor to their hidden finger. This shows that proprioceptive position sense of finger and gaze are not aligned, suggesting that people rely on vision to guide their gaze to their own finger.